In vivo acquisition of blaKPC-2 with low biological cost in blaAFM-1-harboring ST463 hypervirulent Pseudomonas aeruginosa from a patient with hematologic malignancy. (December 2022) - Zhang, Piaopiao; Wang, Jie; Shi, Weixiao; Wang, Nanfei; Jiang, Yan; Chen, Hongchao; Yang, Qing; Qu, Tingting
ABSTRACT: Objectives: Klebsiella pneumoniae carbapenemase (KPC)–producing sequence type (ST) 463 Pseudomonas aeruginosa are increasingly prevalent in China. This study aims to investigate how bla KPC-2 is acquired in ST463 P. aeruginosa during antimicrobial therapy. Methods: Two extensively drug-resistant P. aeruginosa strains, B1122 and U1121, were respectively isolated from blood and urine of a patient during carbapenem therapy. Whole-genome sequences were obtained, and minimum inhibitory concentrations (MICs) were determined. Plasmid transferability and stability were examined. Bacterial growth kinetics, biofilm formation, and virulence level was assessed. Results: U1121 and B1122 were only susceptible to amikacin and intermediately susceptible to colistin. They were isogenic ST463 P. aeruginosa strains and shared the same chromosome-encoded resistance genes, including bla AFM-1 . This is the first report of chromosomal integration of bla AFM-1 in P. aeruginosa mediated by IS CR29 . pU1121 and pB1122, which shared almost identical backbone, were the sole plasmids in U1121 and B1122, respectively, differing by an insertion region containing two copies of bla KPC-2 genes observed on pU1121. Sequence alignment revealed that pU1121 might evolve in vivo from pB1122 via IS 26 -mediated continuous genetic rearrangement in response to selective challenge from carbapenem. pU1121 was not self-transmissible and could be stably maintained in the host in the absence of antibiotic. Both U1121 and B1122 were hypervirulent, and no differences on virulence were recorded between them. However, U1121 exhibited significant impaired growth in comparison with B1122. Conclusion: ST463 P. aeruginosa can capture bla KPC-2 through horizontal transfer of insertion sequence under antibiotic selection pressure, which does decrease the fitness but does not impair the virulence of the ancestor.